Pupils' classroom environment perceptions, attitudes and achievement in science at the upper primary level - Chin, Tan Ying. (2008)
The main aim of this study is to assess pupils' perceptions of their science classroom learning environment in a coeducational government primary school This learning environment comprises both that of the regular science classroom and that of the science laboratory. The study examined pupils' actual and preferred perceptions of their science learning environment, as well as, differences in boys' and girls' perceptions of that environment. Associations between pupils' environmental perceptions, attitudinal and achievement outcomes were also investigated.